Ayurvedic Approach on COVID-19 Prevention and Care - Bhatta, Pramod (Nepal Journal of Multidisciplinary Research, 2020)
CoVID-19 caused pandemic taking lives of more than 551,046 resulting massive physical, psychological, economical loss around the world. Various aspect of epidemic is described in Ayurveda. The study aims to identify the components which can help preventing and caring from Corona Virus and COVID-19. Based on textual and research of previous literatures, the finding is suggestive of by applying the Ayurvedic approach to prevent and care of proper adaptation of health behavior will support preventing the disease and minimize the complications.